OPTIMIZATION OF SURGICAL TACTICS FOR POSTOPERATIVE BILE EFFLUVIUM AND BILIARY PERITONITIS AFTER CHOLECYSTECTOMY - Arziev Ismoil Alievich; Kurbaniyazov Zafar Babazhanovich; Sayinaev Farrukh Karamatovich; Baratov Manon Bahramovich; Nazarov Zokir Norzhigitovich (Zien Journals, 2022)
The paper analyzes the results of surgical treatment of 3266 patients for various forms of GCB. Bile flow and bile peritonitis in the postoperative period were observed in 34 patients due to "small" injuries (aberrant hepatic-bladder ducts of the gallbladder bed - Lushka passages, leakage of the stump of the cystic duct, drainage loss from the choledoch). The developed surgical tactics, based on ultrasound and RPCG data, can improve the results of treatment and avoid relaparotomy in 94.2% of patients with bile flow with "small" lesions of the bile ducts
Keywords: cholecystectomy; bile expulsion; biliary peritonitis; surgical tactics